The Therapeutic Effect of Azole and Probiotic Combination on Vulvovaginal Candidiasis: A Literature Review - Ummu Aiman; Sahda Alfreda Putri; Jeniffer Handiokho; Efenina Ginting; Agnes Amalia; Maureen Miracle Stella (GLOBAL HEALTH SCIENCE GROUP, 2025)
One of the most prevalent vaginal infections in the world is vulvovaginal candidiasis. Due to numerous reported cases of antifungal resistance, a combination treatment with synergistic effect is needed. We aimed to examine the effects of combination therapy involving the administration of azoles and probiotics for treating vulvovaginal candidiasis. A comprehensive search of databases (Google Scholar, PubMed, Wiley, Taylor and Francis, ScienceDirect, and SAGE) using (